We Need to Compare, but How? Measurement Equivalence in Comparative Public Administration. (14th December 2014) - Jilke, Sebastian; Meuleman, Bart; Van de Walle, Steven
Abstract In addition to public administrations and public managers, there is increasing interest in studying citizens' interactions with and views toward government from a comparative perspective in order to put theories to the test using cross‐national surveys. However, this will only succeed if we adequately deal with the diverse ways in which respondents in different countries and regions perceive and respond to survey measures. This article examines the concept of cross‐national measurement equivalence in public administration research and explores methods for establishing equivalence. Two methodologies are examined that test and correct for measurement nonequivalence: multiple‐group confirmatory factor analysis and multilevel mixture item response theory. These techniques are used to test and establish the cross‐national measurement equivalence of two popular measurement constructs: citizen satisfaction with public services and trust in public institutions. Results show that appropriately dealing with nonequivalence accounts for different forms of biases that otherwise would be undetected. The article contributes to the methodological advancement in studying public administration beyond domestic borders.